Bladder Pressure Measurements in Patients Admitted to a Medical Intensive Care Unit. (September 2015) - Anvari, Evamarie; Nantsupawat, Nopakoon; Gard, Ruth; Raj, Rishi; Nugent, Kenneth
Abstract: Background: Intra-abdominal hypertension is identified as an independent risk factor for death. However, this pathophysiological state is not always considered in patients in medical intensive care units and is frequently underdiagnosed. Methods: Serial bladder pressure measurements were recorded in patients admitted to the medical intensive care units to determine the frequency of intra-abdominal hypertension. Results: This study included 53 patients with a mean age of 59.0 ± 17.7 years. The average admission intra-abdominal pressure was 10.0 ± 5.4 mm Hg with a range of 0 to 28 mm Hg. Eleven patients (21%) had an initial pressure reading above normal (>12 mm Hg). Peak airway pressures were higher, and PaO2 /FiO2 ratios were lower in patients with an initial pressure >12 mm Hg. Conclusions: Bladder pressure measurements provide an easy method to estimate intra-abdominal pressures and provide an additional tool for the physiologic assessment of critically ill patients.